Construção e validação de cartilha educativa para prevenção da violência sexual na adolescência - Silva, Kelanne Lima da (2015)
Sexual violence affects all areas of human development, particularly when it occurs in adolescence. Thus, it is necessary that professionals from various sectors of society formulate coping and prevention strategies for sexual violence, facilitating the approach to this theme. With this purpose, educational technologies emerge as auxiliaries in health education activities. In this context, this study aimed to construct and validate a digital educational booklet aimed at preventing sexual violence in adolescence. It is a methodological and validation research developed according to the stages of construction of digital educational materials proposed by Falkembach, which comprised: analysis and planning, through literature review and two focus groups conducted with adolescents at school; modeling; implementation; evaluation; and distribution. After the material construction, the evaluation stage took place, carried out by seven judges in the areas of health education and sexual violence and by 196 adolescents aged between 10 and 13 years on the educational material. The study followed the ethical and legal aspects of research involving human beings, according to CAAE No. 26440614.1.0000.5054. Literature review showed that the consequences of sexual violence were the themes most approached. Results of the focus group show that despite knowing the problem, adolescents reduce the occurrence of sexual violence to rape; consider females more prone to and are unaware of the occurrence of sexual violence in males; consider the offender a maniac and easily identifiable; reveal the reality of domestic violence highlighting the role of father and stepfather; and fail to identify the behaviors that make them more vulnerable to the occurrence of sexual violence. The booklet was constructed based on the results of the literature review and focus groups, presenting information about the concept and types of sexual violence; sexual and reproductive rights; statistics on the occurrence of this injury; the profile of sex offenders; the Internet as a place favorable for the occurrence of sexual violence; and presents how to report offenders and assist victims; laws that protect adolescents, and actions to develop protective attitudes. As for the judges’ validation, all items presented Content Validity Index above 0.8, indicating that the material was validated on the objectives, structure, presentation, and relevance of the booklet. According to the assessment of adolescents, the educational material is relevant, interesting, accessible, well-designed, attractive, and may assist in the adoption of preventive behaviors as regards sexual violence. It is concluded that digital educational booklet can be considered valid for implementation among adolescents in relation to the prevention of sexual violence in an innovative and persuasive way, contributing to health promotion in Basic Health Units and schools. It is recommended that this technology is used by a multidisciplinary team with regard to strategies to prevent sexual violence in adolescence.